Le magazine Fémina (1933-1938) : cuisine et gestion domestique au Portugal - Isabel Drumond Braga (Genre & Histoire)
The Portuguese magazine Fémina, edited by a woman, Helena de Aragão (1880–1961), published during the early years of the Estado Novo (1933–1974), i.e. between 1933 and 1938, is addressed to a female readership. The main goal of this paper is the study of cooking recipes and domestic management, in order to understand how the magazine articles could serve the knowledge of women in the upper and middle classes and be an instrument of female training and discipline.